RECURRENT CONGENITAL PTOSIS MANAGEMENT BY SUPRAMAXIMAL LEVATOR RESECTION TECHNIQUE: Poster Presentation - Case Report - Resident - Desi Kristina Utami; Shanti F. Boesoirie; Raden Angga Kartiwa; Niluh Putu Ayu Dewi Wardhani; Mohamad Rinaldi Dahlan (Majalah Oftalmologi Indonesia, 2023)
Introduction : Congenital ptosis is an abnormal low position of the eyelid since birth. Levator resection technique is one of the surgery technique for ptosis corection. Recurrence could be occured even after ptosis correction Case Illustration : A 22 year old male presented with a chief complaint of droopy left eyelid since birth. Visual aquity were 0,08 pinhole 0,2 and 0,25 pinhole 0,63 respectively. Opthalmology examination revealed interpalpebral fissure (IPF) 4 mm, margin reflex distance (MRD)1 0 mm, MRD2 4 mm and levator function test (LFT) 6 mm on the left eye (Figure 1). Levator resection technique was conducted on his left eye with a good result, MRD1 2 mm, MRD2 5 mm, IPF 7 mm. But the lid dropped again after3 months (Figure 2). Opthalmology examination of the left eye showed IPF 5 mm, MRD1 0 mm, MRD2 5 mm, LFT 2 mm and lagophtalmos 1 mm. Second surgery was done with supramaximal levator resection technique. Good result was achieved after second surgery, MRD1 3 mm, MRD2 5 mm, IPF 8 mm (Figure 3). Discussion : Recurrent ptosis could occured after ptosis surgery and had challenges due to scar from previous surgery. Frontal suspension technique was recommended for congenital ptosis levator function less than 4 mm. Supramaximal levator resection was done for this patient, with resection of 30 mm levator muscle, which had result as good as of frontal suspension technique. Conclusion : Levator resection technique could be repeated to repair recurrent congenital ptosis. Supramaximal levator resection technique is one of the option.